eCM 2007
DOI: 10.22203/ecm.v013a10
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated viral vector transduction of human mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) have received considerable attention in the emerging field of regenerative medicine. One aspect of MSC research focuses on genetically modifying the cells with the aim of enhancing their regenerative potential. Adeno-associated virus (AAV) holds promise as a vector for human gene therapy, primarily due to its lack of pathogenicity and low risk of insertional mutagenesis. However, the existing data pertaining to AAV transduction of MSCs is limited.The objective of this work was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 34 publications
4
58
0
Order By: Relevance
“…In contrast, a vector dose-dependent enhancement in transduction efficiency of 1-65% has been reported in human MSCs, but those authors concluded that host cellular barriers may contribute to the relatively restricted transgene expression observed in MSCs (Stender et al, 2007). Importantly, the AAV2 vector-transduced MSCs in this study retained their multipotential activity compared with the untransduced controls (Stender et al, 2007). Similarly, in fibroblasts, we and others have reported *30-fold lower levels of AAV2 DNA replication when compared with 293 or HeLa cells (Hansen et al, 2000;Bhrigu and Trempe, 2009).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In contrast, a vector dose-dependent enhancement in transduction efficiency of 1-65% has been reported in human MSCs, but those authors concluded that host cellular barriers may contribute to the relatively restricted transgene expression observed in MSCs (Stender et al, 2007). Importantly, the AAV2 vector-transduced MSCs in this study retained their multipotential activity compared with the untransduced controls (Stender et al, 2007). Similarly, in fibroblasts, we and others have reported *30-fold lower levels of AAV2 DNA replication when compared with 293 or HeLa cells (Hansen et al, 2000;Bhrigu and Trempe, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…In murine fibroblasts, the ratelimiting step for AAV-mediated transgene expression appears to be the intracellular trafficking and capsid uncoating steps, as we have demonstrated earlier (Hansen et al, 2000). And, in MSCs, the efficiency of AAV2 vector-mediated transduction has so far been not optimal ( Ju et al, 2004;Kumar et al, 2004;McMahon et al, 2006;Stender et al, 2007). Thus, it is critical to develop novel AAV vectors that can target and transduce both of these cell types at highefficiency, for their widespread applicability in combinatorial gene and cell transfer applications.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…[1][2][3][4][5] The multipotential of MSCs, their relatively easy isolation, culture and ex vivo expansive potential have attracted considerable attention in efforts to develop cell and gene therapies and have made these cells an attractive therapeutic tool in a wide range of clinical applications. 6 During the past decade many different viral vectors including retrovirus, 7 adenovirus, [8][9][10][11][12][13] lentivirus [13][14][15][16] and adeno-associated virus 13,[17][18][19][20] have been utilized to deliver genes to or modify genes in MSCs. Although the viral gene delivery to MSCs has made an impressive advancement toward clinical applications, 21 several drawbacks exist.…”
Section: Introductionmentioning
confidence: 99%